2015
DOI: 10.1016/j.agee.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Trends and spatial variation in water and land footprints of meat and milk production systems in Kenya

Abstract: A B S T R A C TGlobal consumption of livestock products is increasing steadily due to human population growth, poverty reduction and dietary changes raising the demand for already scarce freshwater and land resources. Here, we analyze the changes associated with direct and indirect use of freshwater and land for meat and milk production in three production systems in Kenya between the 1980s and 2000s. We use two resource use indicators, the water footprint (m 3 /year) and land footprint (ha), to assess changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 37 publications
1
41
1
3
Order By: Relevance
“…During this period, camel milk production in Kenya rose from 335,000 tons to 937,000 tons, and meat production from 15,000 tons to 651 000 tons (FAO ). Kenyan land use for milk production has increased for camels at a time when land use for cattle ranching concurrently decreased by half (Bosire et al., ). Camels in Kenya are used primarily for milk production, with a shift from subsistence to market production having increased significantly in the last decade (Musinga et al., ; Hussein Abdi, ; Anderson et al., ; Noor et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, camel milk production in Kenya rose from 335,000 tons to 937,000 tons, and meat production from 15,000 tons to 651 000 tons (FAO ). Kenyan land use for milk production has increased for camels at a time when land use for cattle ranching concurrently decreased by half (Bosire et al., ). Camels in Kenya are used primarily for milk production, with a shift from subsistence to market production having increased significantly in the last decade (Musinga et al., ; Hussein Abdi, ; Anderson et al., ; Noor et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ran et al (2016) indicate that feed quality, digestibility, and feed conversion efficiency impact livestock water productivity. Bosire et al (2015) found diet composition can determine the magnitude of the water footprint of milk, because diet translates into better feed conversion and more efficient use of freshwater. White (2016) showed that management to reduce water consumption of dairy cattle improves the use of protein and energy.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the significant amount of water used in feed production, we found that the feed conversion efficiency for lactating cows is too low. The low feed conversion efficiency leads to a higher water footprint of feed rations [12]. We therefore suggest that careful management of rangelands and pastures to improve feed availability and quality as well as breeding programs that aim at enhancing growth rates and milk yield per cow can improve feed conversion efficiency.…”
Section: Discussionmentioning
confidence: 99%